Evaluation of Clethodim for Weed Control in Alfalfa (Medicago sativa L.) - Idris, Khogali I.; Dongola, Gawahir M.; Elamin, Salah E.; Mahgoub, Babiker, M. (University of Khartoum Journal of Agricultural Sciences, 2023)
A field trial was conducted at Shambat Research Station Farm Khartoum, Sudan during 2011/2012 and 2012/ 2013 winter seasons, to evaluate the activity and selectivity of the herbicide Clethodim (Select super120 EC ) for weed control in alfalfa. The herbicide was tested at 0.036, 0.048 and 0.060 kg a.i. /fed, as post- emergence treatments, 3 weeks after sowing of alfalfa. The most prevailing weed species were sweet signal grass {Brachiaria eruciformis (Sm) Grieseb.}, purple nut sedege (Cyperus rotundus L.) and croton {Chrozophora plicata (Vahl.) A. Juss. Exspreng}. Results showed that the losses due to competition in dry matter yield of alfalfa were 57% and 37% in the first cut, in the first and second seasons, respectively. All herbicide treatments were highly selective to the crop. The herbicide at all rates tested gave consistent and effective control of grassy weeds (81% – 100%). Most of the herbicide treatments significantly increased alfalfa fresh and dry matter yields in comparison with the weedy check